Diastereomer-specific quantification of bioactive hexosylceramides from bacteria and mammals[S] - Johanna von Gerichten; Kerstin Schlosser; Dominic Lamprecht; Ivan Morace; Matthias Eckhardt; Dagmar Wachten; Richard Jennemann; Hermann-Josef Gröne; Matthias Mack; Roger Sandhoff (Journal of Lipid Research, 2017)
Mammals synthesize, cell-type specifically, the diastereomeric hexosylceramides, β-galactosylceramide (GalCer) and β-glucosylceramide (GlcCer), which are involved in several diseases, such as sphingolipidosis, diabetes, chronic kidney diseases, or cancer. In contrast, Bacteroides fragilis, a member of the human gut microbiome, and the marine sponge, Agelas mauritianus, produce α-GalCer, one of the most potent stimulators for invariant natural killer T cells. To dissect the contribution of these individual stereoisomers to pathologies, we established a novel hydrophilic interaction chromatography-based LC-MS2 method and separated (R > 1.5) corresponding diastereomers from each other, independent of their lipid anchors. Testing various bacterial and mammalian samples, we could separate, identify (including the lipid anchor composition), and quantify endogenous β-GlcCer, β-GalCer, and α-GalCer isomers without additional derivatization steps. Thereby, we show a selective decrease of β-GlcCers versus β-GalCers in cell-specific models of GlcCer synthase-deficiency and an increase of specific β-GlcCers due to loss of β-glucoceramidase 2 activity. Vice versa, β-GalCer increased specifically when cerebroside sulfotransferase (Gal3st1) was deleted. We further confirm β-GalCer as substrate of globotriaosylceramide synthase for galabiaosylceramide synthesis and identify additional members of the human gut microbiome to contain immunogenic α-GalCers. Finally, this method is shown to separate corresponding hexosylsphingosine standards, promoting its applicability in further investigations.